The effect of cognitive ability on academic achievement: The mediating role of self-discipline and the moderating role of planning - Shi, Yueqi; Qu, Shaowei (Frontiers in Psychology, 2022)
In this study, 572 secondary school students aged 15-18 years old stage were selected to study the effect of their cognitive ability and self-discipline and planning on academic achievement. Cognitive ability was classified into memory ability, representational ability, information processing ability, logical reasoning ability, and thinking conversion ability, and analyzed the effects of these five ability values on academic achievement. The mediating effect of self-discipline ability between cognitive ability and academic achievement was analyzed using structural equation modeling (SEM), and the moderating role of planning in the mediating effect was analyzed using planning as a moderating variable. The results showed that cognitive ability can have a significant positive effect on academic achievement, while self-discipline plays a partially mediating role between cognitive ability and academic achievement, and the moderating effect of Planning is significant in the second half of the mediating effect, i.e., the effect of self-discipline on academic achievement changes as the level of planning increases, and the mediating effect is stronger in the condition of higher planning, and the mediating model with moderating effect holds.